Results of Vision Examinations of Mentally Handicapped Persons in Toronto - Bader, Dennis; Mayers, Harvey (Canadian Journal of Optometry, 1981)
This paper presents the results of examinations of mentally handicapped persons in Toronto. Discussion is presented concerning the higher prevalence of vision problems in this population.